2021
DOI: 10.14341/probl12799
|View full text |Cite
|
Sign up to set email alerts
|

A deep intronic mutation in AR gene causing androgen insensitivity syndrome: difficulties of diagnostics

Abstract: Partial androgen resistance syndrome (PAIS) is the most difficult form of disorders/differences of sex development 46,XY (DSD 46,XY) for choosing of patient management. To date, there are no clear biochemical criteria, especially before puberty, that allow differentiating PAIS from other PAIS-like forms of DSD 46, XY, and genetic verification of the partial form of AIS plays an important role. Meanwhile, according to the literature, mutations in the coding region of AR gene have not been identified in more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Another study identified deep intronic mutation in intron 6, creating an alternative splice acceptor site of the AR gene, in a family with PAIS patients [24]. The same mutation was found in an unrelated patient, also with PAIS [25]. Deep intronic mutations were observed in CAIS patients [24,26,27].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study identified deep intronic mutation in intron 6, creating an alternative splice acceptor site of the AR gene, in a family with PAIS patients [24]. The same mutation was found in an unrelated patient, also with PAIS [25]. Deep intronic mutations were observed in CAIS patients [24,26,27].…”
Section: Discussionmentioning
confidence: 83%
“…Studying the noncoding region of the AR gene is highly challenging due to its genomic size of 186,500 nucleotides, as compared of only 2763 nucleotides of the coding sequence. However, the probability of identifying pathogenic variants outside of the AR coding regions in AIS patients is high [ 25 ]. Further advancements in genetic diagnostics with the introduction of targeted sequencing of the whole genomic locus of AR gene, using targeted long-read sequencing which also preserves epigenetic information [ 28 , 29 ], could better clarify the role of noncoding variation in AIS.…”
Section: Discussionmentioning
confidence: 99%